The Effect of Linguistic Homogenization on English Proficiency of Students, Case Study: Junior Students of Shahid Sadoughi University of Medical Sciences, 2018 - Kazem Barzegar; Amir Reza Nemat Tabrizi; Manoochehr Jafarigohar; Fereidoon Vahdany (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: Iranian students of health need to bone up on their academic English to be able to read the English sources of health as a factor contributing to community health promotion. In the Iranian academia, students are placed in Basic and General English courses not on the basis of proficiency levels, but on the basis of their academic majors with the same protocol, teaching materials, and methodology used for these heterogeneous classrooms leading to failure and dissatisfaction in the use of academic English as a vehicle for increasing their knowledge of community health. This study investigated the effect of English proficiency homogenization on linguistic proficiency of Iranian students of health as a means of health enhancement via reading English sources. Methods: In this quasi-experimental study conducted in 2018, the Cambridge Placement Test was given to 71 students of three health majors at Shahid Sadoughi University of Medical Sciences selected with convenient sampling method. The students were divided into three language ability groups using placement test percentiles and taught with two different protocols which were used till the midterm exam. The midterm exam was given and the data were collected and analyzed with SPSS20 using descriptive statistics, i.e., frequency, percentiles, mean, and standard deviation and also inferential statistics, i.e., one-way ANOVA, Levene statistic, Tukey HSD, and independent T-test. Results: A significant difference was found between the three groups on the placement test (p=0.015); there was no significant difference among the three different academic majors with regard to Criterion-referenced Test (CRT) scores (p=0.05); there was no significant difference among the three Norm-referenced Test (NRT) forms (Forms A, B, & C) (p=0.05); also, there was a significant difference among the two CRT forms (Forms A, B) (p=0.05). Regarding the placement test, the significance indices demonstrated a significant difference between group A, on the one hand, and groups B and C, on the other with no significant difference between groups B and C (p=0.05). The findings of the second part of the post hoc test showed a significant difference for the midterm exam between Group A, on the one hand, and Group B and Group C (p=0.05), on the other, with no significant difference between groups B and C (p=0.05), indicating the success of the present study. Conclusion: The students of health should be grouped in Basic English and EGP courses, not based on their academic majors, but based on their English proficiency levels for a successful English pedagogy leading to successful use of English texts of health as a means of promoting health community.